The effectiveness of transactional analysis therapy, schema therapy, and emotionally focused therapy on interpersonal forgiveness among university students experiencing emotional failure - Dehghani Neyestani, Hadi; Atashpour, Seyed Hamid; Torkan, Hajar (Researcher Bulletin of Medical Sciences, 2026)
Objective: University students are particularly vulnerable to emotional distress, especially during times of academic pressure, relationship challenges, or personal loss. Emotional failure can lead to negative emotional states, such as anger, resentment, and bitterness, which can hinder personal growth and interpersonal relationships. This study investigated the effectiveness of interpersonal analysis group therapy, schema therapy, and emotionally focused therapy on interpersonal forgiveness among university students experiencing emotional failure. Materials and Methods: This study utilized a quasi-experimental pre-test-post-test control group design. A convenience sample of 60 participants was randomly assigned to one of four groups: transactional analysis therapy, schema therapy, emotionally focused therapy, or a control group. The Interpersonal Forgiveness Measurement Questionnaire (IFMQ) was administered to collect pre- and post-intervention data. Data analysis was conducted using SPSS version 22, employing analysis of covariance and Bonferroni post hoc tests. Results: The findings revealed that transactional analysis therapy, schema therapy, and emotionally focused therapy significantly enhanced interpersonal forgiveness in university students experiencing emotional failure compared to the control group (P<0.001). Moreover, no statistically significant differences were observed among the effects of these three therapeutic interventions on interpersonal forgiveness in this population. Conclusion: The study found that transactional analysis therapy, schema therapy, and emotionally focused therapy were all effective in increasing interpersonal forgiveness among university students who had experienced emotional failure. This suggests that psychotherapists can choose any of these therapies based on the individual needs of their clients.